Analisis Senyawa Fitokimia dari Ekstrak Maggot Black Soldier Fly (Hermetia illucens) - Adinda Refa Shabira; Luthfi Hana Fadiah; Muhimatul Umami (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2025)
This study aims to determine the phytochemical content of Black Soldier Fly (BSF) larvae extract, also known as Hermitia illucens. The maceration method with 96% ethanol solvent was used for extraction, followed by evaporation using a rotation evaporator. Qualitative phytochemical tests were carried out to identify compounds such as alkaloids, flavonoids, saponins, terpenoids, polyphenols, steroids, and triterpenoids. The results showed that BSF maggot extract contained alkaloid and flavonoid compounds that were positively detected, while other compounds were not detected by the method used. The alkaloid and flavonoid content has antimicrobial, anti-inflammatory, and antioxidant properties. These results indicate that BSF larvae can function as a source of natural biopharmaceutical active ingredients. However, the type of solvent used and the process conditions used affect the success of the extraction.